KNOWLEDGE AND OPINION OF TEENAGERS ON ABORTION - Brêtas, José Roberto da Silva; Zanatta, Luiz Fabiano; Moraes, Silvia Piedade de; Freitas, Maria José Dias de; Goellner, Maila Beatriz (Journal of Health Care, 2017)
Introduction: The topic of abortion still allows multiple interpretations and represents diverse interests for social institutions, among which there is no consensus on the issue, even though it is considered a serious public health problem. Objective: To identify the knowledge and opinion of high school adolescents about abortion, observing which variables change according to the higher level of schooling. Method: This is a descriptive study involving 302 adolescents of both sexes, between the ages of 14 and 20 years old, who attended high school in three state schools in the city of Embu das Artes (São Paulo, Brazil). A semi-structured, multiple-choice, self-administered questionnaire was used as data collection tool in the classroom. Results: The obtained data showed that there is a strong influence of religious and moral concepts in the structuring of knowledge on the subject, which have modulated opinions about the legislation in force in the country. Regarding abortion methods, a higher percentage of adolescents know about minor surgeries (50.66%), followed by marijuana tea (34.43%) and pointed objects (27.48%). Regarding the sources of information on abortion, statistically significant results were detected only for magazine/newspaper (p=0.001) and TV (p=0.003). Concerning the opinion on the theme, 55.63% of the participants were against abortion and 82.45% were in favor in cases of pregnancy resulting from rape. Conclusion: The formulation of knowledge on the subject was based on legality, increasing its intensity according to the higher schooling of the respondents, while the opinion of the participants reflected the dominant social ideals on the subject.